2020
DOI: 10.1158/1055-9965.epi-19-1375
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Trust of Cancer Information among Hispanic Adults in the United States: An Analysis of the Health Information National Trends Survey

Abstract: Background: Hispanics are differentially burdened by inequities in cancer outcomes. Increasing knowledge about cancer and cancer services among Hispanics may aid in reducing inequities, but little is known about what information sources are considered most effective or most trusted by this diverse population. The goal of this study was to examine heterogeneity in trust of cancer information from various media sources among U.S. Hispanic adults.Methods: Using data from the Health Information National Trends Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…These differences may be attributable to differences in health literacy, difficulties and frustration in accessing online information, or trust in health information from online sources [ 23 , 24 , 27 , 45 , 46 , 47 , 48 , 49 , 50 ]. Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These differences may be attributable to differences in health literacy, difficulties and frustration in accessing online information, or trust in health information from online sources [ 23 , 24 , 27 , 45 , 46 , 47 , 48 , 49 , 50 ]. Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ]. Lastly, we observed that older adults were less likely to use social media or online groups for seeking and sharing health information as well as for social support.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This occurred despite the increasing incidence of COVID-19 throughout that time period in the Los Angeles area [ 2 ]. This could be due to increased familiarity with the COVID-19 virus leading to increased risk tolerance among our population [ 3 ]. This occurred in the absence of any significant public health intervention encouraging people to access medical care.…”
mentioning
confidence: 99%